THE INFLUENCE OF PRICE, SERVICE QUALITY, AND LIFESTYLE ON THE PURCHASE DECISION OF ORNAMENTAL PLANTS DURING THE COVID-19 PANDEMIC: (A Study on Visitors of Madirsan Flower Tourism Village) - Diah Pratiwi, Adinda Uci; Mardhiyah, Ainun (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Consumer purchase decisions, whether to buy a product or not, are influenced by several key factors, including service quality, lifestyle, and price. This holds true for the current trend of increased ornamental plant purchases, particularly during the pandemic, which has notably boosted sales at the Madirsan Flower Tourism Village. This study's primary objectives were to assess the impact of price, service quality, and lifestyle on the purchasing decisions related to ornamental plants within the Madirsan Flower Tourism Village during the COVID-19 pandemic. Quantitative research methods were employed, with a sample of 100 respondents from the Medan and Deli Serdang regions, selected using the classical formula for sampling. Data were collected via questionnaires using the Likert scale, and the analysis involved instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing through tools like MS Excel and SPSS 23. The findings of this research underscore that price, service quality, and lifestyle all play significant and positive roles in influencing purchasing decisions among the residents of Medan City and Deli Serdang. This suggests that businesses operating within the ornamental plant sector should consider these factors carefully to optimize their strategies, especially in the context of the ongoing pandemic.